2022
DOI: 10.21037/jtd-21-1782
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter closure of inferior sinus venosus defect using a patent ductus arteriosus occluder following simulation with a 3D-printed model

Abstract: Background Transcatheter closure of inferior sinus venosus defect (ISVD) is still contraindication. To explore whether transcatheter closure with patent ductus arteriosus (PDA) occluders is possible for ISVD. Methods From June 2014 to March 2021, 12 patients were recruited diagnosed as <25 mm ISVD. The three-dimensional printing (3DP) heart model was produced based on multi-slice computed tomography (MSCT) scans. Preoperative closure simulation was planned on the person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, this was a retrospective, nonrandomized study that included a small cohort and no comparative group; additional randomized studies with longer follow‐up periods would be required to confirm the superiority of covered stent implantation over the surgical approach in the management of these patients. Another recent study of 12 patients with inferior sinus venosus‐type ASD who underwent successful transcatheter closure using PDA occluders and three‐dimensional‐printed heart models reported that interventional therapy may not be contraindicated in patients with inferior sinus venosus‐type ASD 143 . However, this previous study was a retrospective study with a small sample size, and prospective, randomized controlled trials including a large cohort of patients are necessary.…”
Section: Atrial Septal Defectmentioning
confidence: 93%
See 1 more Smart Citation
“…However, this was a retrospective, nonrandomized study that included a small cohort and no comparative group; additional randomized studies with longer follow‐up periods would be required to confirm the superiority of covered stent implantation over the surgical approach in the management of these patients. Another recent study of 12 patients with inferior sinus venosus‐type ASD who underwent successful transcatheter closure using PDA occluders and three‐dimensional‐printed heart models reported that interventional therapy may not be contraindicated in patients with inferior sinus venosus‐type ASD 143 . However, this previous study was a retrospective study with a small sample size, and prospective, randomized controlled trials including a large cohort of patients are necessary.…”
Section: Atrial Septal Defectmentioning
confidence: 93%
“…Another recent study of 12 patients with inferior sinus venosus-type ASD who underwent successful transcatheter closure using PDA occluders and three-dimensional-printed heart models reported that interventional therapy may not be contraindicated in patients with inferior sinus venosus-type ASD. 143 However, this previous study was a retrospective study with a small sample size, and prospective, randomized controlled trials including a large cohort of patients are necessary. At this time, the surgical repair remains the standard treatments in patients with sinus venosus-type ASD.…”
Section: Advanced Transcatheter Closure Of Asdmentioning
confidence: 99%